2022
DOI: 10.3904/kjim.2022.069
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and clinical impact of COVID-19-associated pulmonary aspergillosis: Multicenter retrospective cohort study

Abstract: Background/Aims: The risk factors and clinical impacts of coronavirus disease 2019 (COVID-19)-associated pulmonary aspergillosis (CAPA) remain controversial, and no data have been reported in Korea. This study aimed to investigate the epidemiology and importance of CAPA diagnostic efforts and to identify the predictors of CAPA and the impacts on clinical outcomes.Methods: Between January 2020 and May 2021, data of severely to critically ill COVID-19 patients were extracted from seven hospitals of the Catholic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…I had the opportunity to contribute to an editorial on a recent article regarding the incidence of invasive pulmonary aspergillosis in critically ill patients diagnosed with coronavirus disease 2019 (COVID-19) [ 1 ]. While many studies are focused on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection itself, it is important to note that COVID-19 has led to various prognostic changes in many other common diseases.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…I had the opportunity to contribute to an editorial on a recent article regarding the incidence of invasive pulmonary aspergillosis in critically ill patients diagnosed with coronavirus disease 2019 (COVID-19) [ 1 ]. While many studies are focused on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection itself, it is important to note that COVID-19 has led to various prognostic changes in many other common diseases.…”
mentioning
confidence: 99%
“…Recently, Lee et al [ 1 ] reported that the incidence of CAPA in the Republic of Korea (ROK) was 11.2% among ICU patients with COVID-19. These data are comparable with findings from a multicenter retrospective study in the ROK [ 5 ].…”
mentioning
confidence: 99%
See 3 more Smart Citations